Renewable Energy Use in Green Hotels for Sustainability: A Systematic Review - Ghimire, Bhawani Thapa; Muneenam, Umaporn; Techato, Kuaanan (International Journal of Energy Economics and Policy, 2023)
This article studies the use of renewable energy in hotels as a means of promoting green practices and sustainability. The objective of the study is to previous research studies on renewable energy use in hotels and green practices. It is based on articles published in different journals between 2008 to 2023. Out of the initial 16500 articles screened by Google scholars and 1373 from Base, the matched topic was 200, after further screening 61 articles were selected for final review. Renewable energy use and green practices have been adopted by many hotels with sustainability practices. The study shows that many hotels have adopted renewable energy and green practices to promote sustainability. However, future research should focus on the relationship between the specific types of renewable energy used in hotels and their impact on green practices and sustainability.